Taxonomic review of weevils of the tribe Celeuthetini, mainly from Sundaland, Sulawesi and the Lesser Sunda Islands (Coleoptera, Curculionidae, Entiminae) - Riedel, Alexander (Zootaxa, 2024)
Type material of species belonging to the weevil tribe Celeuthetini Lacordaire, 1863 mainly from Sundaland, Sulawesi and the Lesser Sunda Islands was studied. Mitochondrial sequence data could be obtained for 27 old type specimens, providing important evidence on their systematic placement. Various taxonomic problems evident from molecular and morphological data are remedied. Nusasyntrophus Riedel gen. n., Parasyntrophus Riedel gen. n., and Apotomorhamphus geminus Riedel sp. n. are described. The following genera are junior synonyms of Piezonotus Schoenherr, 1834: Coptorhynchus Guérin-Méneville, 1841 (syn. n.), Picronotus Marshall, 1956 (syn. n.), Platyspartus Faust, 1897 (syn. n.). Colpomus Marshall, 1956 is a junior synonym of Enaptomias Faust, 1897 (syn. n.) and Aulacophrys Marshall, 1956 is a junior synonym of Apiezonotus Heller, 1941. Coptorhynchus ternatensis Guérin-Méneville, 1841 and Isomerinthus asper Pascoe, 1881 are transferred to Piezonotus Schoenherr, 1834: Piezonotus ternatensis (Guérin-Méneville, 1841) (comb.n.), Piezonotus asper (Pascoe, 1881) (comb.n.). New synonymies are proposed for the following species: Syntrophus carinicollis (Heller, 1914) = Syntrophus costicollis Marshall, 1956 (syn. n.); Syntrophus echinatus (Heller, 1900) = Syntrophus bipusulosus (Heller, 1940) (syn. n.). Apotomorrhamphus heteroglymmoides Günther, 1938 and A. femoratus Voss, 1940 are transferred to Heteroglymma Faust, 1897: Heteroglymma heteroglymmoides (Günther, 1938) comb.n., Heteroglymma femoratum (Voss, 1940) comb.n.; Heteroglymma bispinosa Heller, 1900 and Heteroglymma hoplocnemis Günther, 1938 are transferred to Atactoglymma Heller, 1900: A. bispinosum (Heller, 1900) comb. n., A. hoplocnemis (Günther, 1938) comb. n.; Heteroglymma carinuliferum Heller, 1914 is transferred to Javaulius Marshall, 1956: Javaulius carinulifer (Heller, 1914) comb.n.; Idiopsodes gitgitus (Heller, 1914), Idiopsodes radiatifrons (Heller, 1914), and Idiopsodes setosapex (Heller, 1914) are transferred to Parasyntrophus gen. n.: Parasyntrophus gitgitus (Heller, 1914) comb. n., P. radiatifrons (Heller, 1914) comb. n., P. setosapex (Heller, 1914) comb. n.; Phraotes nodifer Voss, 1940 is transferred to Bonthaina Heller: Bonthaina nodifera (Voss, 1940) comb. n. Piezonotus humeralis Heller, 1914 is transferred to Temnogastrus Marshall, 1956: Temnogastrus humeralis (Heller, 1914) comb. n.; Heteroglymma echinatum Heller, 1900 and Trigonops bipusulosa Heller, 1940 are transferred to Nusasyntrophus gen. n.: Nusasyntrophus echinatus (Heller, 1900) comb. n., Nusasyntrophus bipusulosus (Heller, 1940) comb. n. Nusasyntrophus echinatus virescens (Heller, 1914) and Tarunus wolterecki banggaiensis (Günther, 1938) are elevated to species status: N. virescens (Heller, 1914) stat. n., comb. n., Tarunus banggaiensis (Günther, 1938) stat. n. Apotomorrhamphus parcesetosus Voss, 1940 is resurrected from synonymy with A. splendens Faust, 1897. Bonthaina solitaria Heller, 1900 is designated type species of Bonthaina Heller, 1900. Lectotypes are designated for the following names: Apotomorhamphus sarasini Faust, Apotomorhamphus splendens Faust, 1897, Borneobius curvipes Marshall, 1956, Coptorrhynchus beccarii Pascoe, 1885, Coptorrhynchus wolterecki banggaiensis Günther, 1938, Coptorrhynchus wolterecki Günther, 1938, Heteroglymma bispinosum Heller, 1900, Heteroglymma carinicolle Heller, 1914, Heteroglymma carinuliferum Heller, 1914, Heteroglymma echinatum Heller, 1900, Heteroglymma echinatum virescens Heller, 1914, Heteroglymma setosum Marshall, 1925, Idiopsis gitgita Heller, 1914, Idiopsis radiatifrons Heller, 1914, Idiopsis setosapex Heller, 1914, Isomerinthus asper Pascoe, 1881, Javaulius rudis Marshall, 1956, Javaulius subvirens Marshall, 1956, Piezonotus suturalis Gyllenhal, 1834, Trigonops kombuisana Marshall, 1925, Trigonops renschi Heller, 1940, Trigonops tuberculata Faust, 1896, Piezonotus humeralis Heller, 1914, Piezonotus javanus Faust, 1896, Sphaeropterus gramineus Pascoe, 1881. Piezonotus suturalis Gyllenhal, 1834 is an endemic to the South Moluccas and its record for Java in the original description is erroneous. The genus Heteroglymma Faust, 1897 is redefined based on a ventral blunt tooth of the protibia. Some characters traditionally used for diagnosis of genera are briefly discussed. Apodemes attached to the body of the penis by flexible loops are discovered in the genera Apotomorhamphus Faust, 1897, Bonthaina Heller, 1900, and Nothes Marshall, 1956. A key to the genera of Celeuthetini from Sundaland, Sulawesi and the Lesser Sunda Islands is provided. Keys to the species are provided for the following genera: Apotomorhamphus Faust, 1897 (only species from Mt. Lompobattang), Bonthaina Heller, 1900, Javaulius Marshall, 1956, Nusasyntrophus gen. n., Parasyntrophus gen. n., Temnogastrus Marshall, 1956.